2021
DOI: 10.1016/j.dhjo.2020.100965
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, social support, social isolation and wellbeing among working age adults with and without disability: Cross-sectional study

Abstract: Background Loneliness is significantly related to health and wellbeing. However, there is little information on the prevalence of loneliness among people with disability or the association between disability, loneliness and wellbeing. Objective/hypothesis For a nationally representative sample of adults (age 16–64) with/without disability, to examine exposure to three indicators of low social connectedness (loneliness, low perceived social support, social isolation), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(147 citation statements)
references
References 32 publications
6
116
0
1
Order By: Relevance
“…Such psychological reactions due to the decline of social relations are more evident in traditional cultures; researchers have shown that decreased emotional contact and feelings of connection with family and friends are associated with symptoms of distress and depression in African-Americans ( Taylor et al, 2016 , 2020 ). Recent studies have shown that social distancing by creating a sense of loneliness, anxiety, suicide ideations ( Armbruster and Klotzbücher, 2020 ), low perception of social support, and an inability to connect with others is associated with low well-being and low sense of social connectedness ( Emerson et al, 2020 ; Garcia et al, 2020 ). In addition to the personal effects of the lockdown, home quarantine and social distancing challenged the value and the cost of relationships with others.…”
Section: Introductionmentioning
confidence: 99%
“…Such psychological reactions due to the decline of social relations are more evident in traditional cultures; researchers have shown that decreased emotional contact and feelings of connection with family and friends are associated with symptoms of distress and depression in African-Americans ( Taylor et al, 2016 , 2020 ). Recent studies have shown that social distancing by creating a sense of loneliness, anxiety, suicide ideations ( Armbruster and Klotzbücher, 2020 ), low perception of social support, and an inability to connect with others is associated with low well-being and low sense of social connectedness ( Emerson et al, 2020 ; Garcia et al, 2020 ). In addition to the personal effects of the lockdown, home quarantine and social distancing challenged the value and the cost of relationships with others.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies have explored the relationship of loneliness, isolation and living alone on the health and well-being of older people. LIL may cause depression, cardiovascular disease, reduced quality of life, low self-rated health, anxiety, reduced cognitive or physical function, frailty, insomnia, mortality, suicide, and work disability in older adults [ 1 , 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Such negative effects may be worse for individuals with lower education, lower income, and disability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The factors related to LIL can be viewed by individual level (demographics, health and psychological characteristics), interpersonal level (family relationship and marital status), and society level (culture, social environment and age friendliness). The factors include age, sex, race, education, socioeconomic status, marital status or widowhood, working status, having children or not, social relationship with friends and neighbors, social anxiety, Internet use, self-rated health, disability, resilience, previous depression, and built environment [ 10 , 21 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In addition, social participation [ 44 ], activity engagement [ 45 ], bonding social capital [ 46 ], and religious belief or spirituality [ 47 , 48 ] may also be protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…The no‐touch guidelines not only made it difficult to diagnose a patient without touching them (Siekmans et al., 2017), but the isolation faced by Ebola patients was found to compromise the nurses’ ability to convey connection and provide comfort to patients in times of distress (Connor, 2015). Such measures, while intended to keep people safe, have concerning short‐ and longer‐term implications on the health of already isolated individuals such as people who are ill, older people (Armitage & Nellums, 2020) and people with disabilities (Emerson, Fortune, Llewellyn, & Stancliffe, 2020).…”
mentioning
confidence: 99%